Groundnut Seed System in Odisha - Khuntia, Debi Prasanna; Mallik, Nagendra Kumar; Nayak, Rozalin (Indian Farming, 2018)
In the state of Odisha, certain factors are the cause for low and f l u c t u a t i n g pr o d u c t i o n of growndnent. The single largest constraint is the non-availailility of quality seed of recommended varieties. Measures and steps required to overcome these constraints have been suggested by the authors of this article, which will help Odisha to tide over the difficulty of quality groundnut seeds for uncreased production.